An efficient certificateless deniable authentication protocol without pairings. (2015) - Jin, Chunhua; Xu, Chunxiang; Zhang, Xiaojun; Li, Fagen
A deniable authentication protocol enables an intended receiver to identify the source of a given message, but the receiver cannot prove the source of a given message to any third party. It is very useful in some particular applications such as electronic voting, online negotiation and online shopping. However, many related protocols are lack of formal security proof which is very important for cryptographic protocol design. In this paper, we present a certificateless deniable authentication protocol. Our protocol is based on certificateless cryptography, which can solve the public key certificate management problem of public key infrastructure (PKI)-based cryptography and the key escrow problem of identity-based cryptography. Our protocol does not need the pairing operation which is the most time-consuming. In addition, our protocol can admit formal security proof in the random oracle model and resist key compromise impersonation (KCI) attack. Compared with the existing deniable authentication protocols, our protocol can be well applied in electronic voting system.